Globalization - Merino, Noël, editor 522928; Gale Group (Online service) 651863 (Farmington Hills, Michigan : Greenhaven Press, 2010)
Explores the issue of globalization by placing opinions from a wide range of sources in a pro/con format. Features articles that express various perspectives on this topic.